(untitled) (Journal of Association of Clinical Endocrinologist and Diabetologist of Bangladesh, 2025)
Background: Infection is an important cause of hospitalization among people with diabetes mellitus (DM). Existing literature exhibits a scarcity of comparative studies analyzing infectious disease profiles in hospitalized patients with diabetes mellitus versus those without the condition. Objective: To compare the infectious disease pattern and infection-related complications between people with or without DM admitted to a non-surgical ward. Methods: This cross-sectional study included hospitalized patients from a general medicine ward of a medical college hospital over two years by convenient sampling. Participants with dengue fever, COVID-19, undiagnosed, or incomplete demographic information were excluded. A semi-structured case record form was used to document the study participants’ demographic, clinical, biochemical data, and culture-sensitivity reports. Results: A total of 276 patients (DM 123 and non-DM 153) were included in the study. Only 14.6% of DM patients had good glycemic control. Urinary tract (UTI) and respiratory tract infection (RTI) were most prevalent in the DM and non-DM groups. However, the frequency of UTI was higher in the DM group (57.7% vs. 32.3%, adjusted residuals: ±4.2), but the RTI frequency was similar (26.8% vs. 22.2%) between the groups. DM patients with UTI showed a higher number of growths of microorganisms on culture media (63.6% vs. 23.8%, p=0.003), with diverse microorganism patterns (Escherichia coli: 64% and Klebsiella: 21%) compared to non-DM (E. coli 80%). Gastrointestinal infection (19.6% vs. 4.9%, p<0.05) and blood infection (enteric fever, sepsis, meningitis) (22.2% vs. 8.1%, p<0.05) were more common in the non-DM group compared to DM. Conclusion: Individuals with DM exhibited a distinct infection pattern from those without DM during hospitalization. J Assoc Clin Endocrinol Diabetol Bangladesh, July 2025;4(2): 50-56